Lacunas no curso de ciências contábeis para adequada formação de profissional da área, do ponto de vista de uma universidade corporativa - Citeroni, Sergio (2014)
The purpose of this study is to investigate possible deficiencies in university accounting courses regarding appropriate vocational training, from the point of view of a corporate university. This is because at almost all professional events, from national seminars to meetings with a small number of participants, as well as the activities of professional associations, there is discussion about the quality of Brazilian professionals, in particular recent accounting graduates. The reason for including topics related to the quality of accounting education in these events is the growing concern amongst executives, market representatives, regulators, professional and trade associations and other stakeholders over the challenges that already exist for accountants and accounting students. It is necessary to understand that the country s university education must foster individual development that is committed to the needs of the market and capable of encouraging scientific and critical thinking in a broader process of knowledge building. To this end, a case study was performed that, firstly, was developed in Ernst & Young and its Corporate University, through interviews with the Executive Director of the said University, based on the company s recruitment process. Secondly, there were interviews with two coordinators of accounting graduation courses, intended to give a better understanding of the organization of the curriculum and its shortcomings. Thirdly, a document prepared by two leading researchers on the search for quality in university accounting education and the Report on the Observance of Standards and Codes were analyzed. Based on the results obtained it was concluded that, independent of opinion and market demand, there is a convergence between theoretical participants, professional educators and development banks regarding the need for change and qualitative aggregation in the training of accounting professionals, and in this study corporate universities are shown to be one answer to this qualitative level required by contemporary society